Pengelolaan Wisata Air Berwawasan Kesehatan Pemetaan Kasus Leptospirosis Faktor Perilaku dan Lingkungan - Rohman, Hendra; Kiswantoro, Amin; Adelia, Dinda (Sekolah Tinggi Pariwisata AMPTA, 2020)
Community behavior and environmental conditions are very potential for leptospirosis cases. The main source of transmission is strongly suspected to be in the vicinity of residential neighborhoods that have standing water and the presence of rats. The aims to identify leptospirosis cases, behavioral and environmental factors for empowering the management of health oriented water tourism. Method: Descriptive with cross sectional design. Results: People bathing and washing clothes at water sources around the water attractions. Water swallowed while swimming or submerging the body has been contaminated with bacteria. Water tourism managers make efforts to minimize the breeding grounds of rats. Conclusion: Health oriented management can develop the potential and attractiveness of tourists. A history of water travel can increase the risk of leptospirosis